PEMBELAJARAN KOOPERATIF DENGAN PENDEKATAN NUMBERED HEAD TOGETHER DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA - Abd Fatah (Prodi Pendidikan Matematika FKIP Universitas Madura, 2021)
The objectives of this study are: 1) To determine the differences in learning outcomes shown by students who learn using the NHT-type cooperative model and conventional learning on the learning outcomes of vocational school students in Sampang on the subject of financial mathematics (annuity). 2) the difference in learning outcomes shown by students who have high learning motivation with students who have low learning motivation towards learning outcomes of vocational school students in Sampang on the subject of annuity. 3) To determine the interaction between the use of the cooperative learning model type NHT and conventional learning, as well as student motivation on learning outcomes of vocational students in Sampang on the subject of annuity. This type of research is an experiment with research subjects of class XII students, the instruments are tests and questionnaires. The homogeneity of the research subjects was tested by using the independent sample test. Data normality was tested with one sample Kolmogorov-Smirnov. Hypothesis testing uses two way ANOVA by displaying the average value of descriptive statistics as a level of differentiation. Based on the results of the study it can be concluded that: 1) There are differences in learning outcomes shown by students who learn using the NHT type cooperative model and accepted conventional learning with a significance level of 0.000 (<0.05). The highest mean is found in the NHT type learning model which in total obtained results of 89.27. 2). There are differences in learning outcomes shown by students who have high learning motivation with students who have low learning motivation who are accepted with a significance level of 0.000 (<0.05). The highest mean is found in high learning motivation, which in total is 88.84. 3) There is a significant interaction between the NHT type learning model, conventional and learning motivation on student learning outcomes on the subject of annuities received at a significance level of 0.001 (<0.05). While the highest mean is found in the interaction between the NHT type learning model with learning motivation of 89.74.